Knowledge landscape of open access in academic libraries through bibliometric analysis 2020-2025 - Bestari, Melati Purba; Yuadi, Imam; Albigaeri, Syahruly Nizar (Universitas Padjadjaran, 2025)
Background: The digital era transformation has changed the role of academic libraries, which initially served as repositories for physical collections and have evolved into facilitators of digital information access and initiators of change in open-access management. The COVID-19 pandemic accelerated the adoption of open access due to the urgent need for unrestricted access to scientific information. Purpose: This study aimed to map the knowledge landscape of open access in academic libraries through a comprehensive bibliometric approach for 2020-2025, identifying dominant themes, intellectual structures, collaboration patterns, and emerging trends. Methods: Data were collected from the Scopus database using the TITLE-ABS-KEY search strategy (